PENGARUH PEMBELAJARAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN NILAI MORAL PADA ANAK USIA 5-6 TAHUN DI PAUD SYAKHSHIATUL UMMAH DESA LIMBAT JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Wenda Wahyuni; Daviq Chairilsyah; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Picture and picture model of learning is a learning model that uses images and matched or sorted into a logical sequence. In picture and picture learning model provides a foundation for developing the child's ability and essential for social activities, personal, and moral. Teachers should be able to create an atmosphere of active learning, innovative, creative and fun. Based on the phenomenon, there are still children who do not want to wash hands after eating and wiped his hands kebaju, there are still children who spoke to the teacher using a high note, indifferent, there are still children who show impatient with the way shouted, while waiting their turn to play and children are still not accustomed to restore the toy in place when I have often reminded by the teacher. For this study aims to determine the influence of the learning model of picture and picture in enhancing moral values of children aged 5-6 years. Obtained results: before using the learning model picture and picture the child in middle category with a total percentage of 88.24% and after using the learning model picture and picture, children are at high category with a total percentage of 70.6%. From the overall results are the effect of picture and picture model of learning in improving the child's moral values on the percentage of 34.3%.Keywords: Picture and picture,morality,children,teacher